Radial: Time to Go Distal - Aqel, Raed; Alzughayyar, Tareq Z.; Misk, Rami A. (Cardiology and Cardiovascular Medicine, 2019)
Background: trans-radial (snuffbox) approach is a newer approach for coronary catheterization with more advantages as compared with the classic anterior trans-radial approach. However, its routine use is still controversial due to the lack of data. Objective: This study aims at evaluating the effectiveness and safety of routine distal right radial (snuffbox) as a route for cardiac catheterization. Materials and Methods: A retrospective chart review of 200 consecutive cardiac catheterization cases performed over 4 months. The distal right radial artery was accessed without ultrasound guidance in all cases, the default access was a distal left radial artery. Information regarding procedure details, success rates and cannulation times were tabulated. Records of patients follow up at 1 to 2-weeks interval post-angiography were recorded. Results: Distal right radial artery access was successful without ultrasound guidance in 98%, the mean cannulation time was (1.35 ± 0.55 min). No complications were recorded at one to two weeks follow up. Conclusion: Distal radial artery catheterization can be performed routinely with high success and safety profiles.